Empirical Model for Landslides Susceptibility in the Himachal Pradesh - Dr. Sanjay Shahi (International Journal of Engineering and Management Research, 2019)
Many natural and man-made hazards affect Himachal Pradesh in India. Even though there are various dangers in the state, landslides are the most common and occur most frequently during the rainy season. Existing research aims to understand the current state of knowledge in Himachal Pradesh about the management of landslide hazards. Landslide disasters in the state are well managed under the state's established policy. Landslide susceptibility zonation maps prepared using GIS have been shown to be the primary method of preventing landslides, while geotechnical investigations of soil have been found to aid in the determination of possible mitigation techniques. Software like Plaxis 2d is proven to be extremely useful in analysing slopes and the effectiveness of solutions.